Barriers to Pursuing Emergency Medicine Specialty Among Iranian General Practitioners: A Cross-Sectional Study - farzaneh raaii; Shahrad Tajaddini; Amin Saberinia; Mohammad Hossein Ahmadi Zarandi (Archives of Academic Emergency Medicine)
Introduction: Although emergency medicine is crucial globally, it remains underdeveloped in Iran, facing low recruitment rates. This study aimed to explore barriers deterring Iranian general practitioners (GPs) from pursuing emergency medicine as a specialty.